2011
DOI: 10.1016/j.ijthermalsci.2010.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Pore scale 3D modelling of heat and mass transfer in the gas diffusion layer and cathode channel of a PEM fuel cell

Abstract: a b s t r a c tFlooding of the gas diffusion layer (GDL) of proton exchange membrane (PEM) fuel cells can be a bottleneck to the system's efficiency and even durability under certain operating conditions. Due to the small scale and complex geometry of the materials involved, detailed insight into the pore scale phenomena that take place are difficult to measure or simulate. In the present effort, a direct 3D microscale model of a portion of the PEM cathode channel and carbon cloth GDL is used to parametrically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…(27) [21] is in general agreement with the data calculated by computational fluid dynamics simulation in [30] for the 40 ppi foam but it underestimates the heat transfer coefficient by ~ 25% if the exhaust gas side is filled with a 10 ppi foam. Therefore some "fine tuning" of Eq.…”
Section: Metal Foamsupporting
confidence: 76%
See 2 more Smart Citations
“…(27) [21] is in general agreement with the data calculated by computational fluid dynamics simulation in [30] for the 40 ppi foam but it underestimates the heat transfer coefficient by ~ 25% if the exhaust gas side is filled with a 10 ppi foam. Therefore some "fine tuning" of Eq.…”
Section: Metal Foamsupporting
confidence: 76%
“…(25) is used [20]. Kopanidis et al [30] were used and found very close to the value of the porosity of the material.…”
Section: Metal Foammentioning
confidence: 83%
See 1 more Smart Citation
“…Numerical simulations of the water transport through different types of GDL were carried out in numerous investigations [344][345][346][347][348][349][350][351][352][353][354][355][356][357][358]. The majority of these two-and three-dimensional models suggest that the transport of liquid water through GDL is mainly dominated by the hydrophobic and morphological properties of the GDL including porosity, tortuosity, cross sectional area, thickness, and PTFE loading.…”
Section: Mea and Gdl Structurementioning
confidence: 99%
“…Fuel cells are a developing energy technology, which offers major advantages and wide range of applications for mobile, transportation and stationary systems [1]. These advantages include high energy efficiency, quiet operation without vibration, portability and almost zero emissions [2].…”
Section: Introductionmentioning
confidence: 99%